The role of physical education and sports in eliminating psychological pressures in practices and non-practices - Abbas Salih, Naseema (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the research is to identify the psychological pressures of university students practices to study sports education and to identify the psychological pressures non-practice university students to study sports education and to identify the role of sports education in eliminating psychological pressures in university students practices and non-practices of the experimental groups and officers in the pre- and posttests, and the researcher assumed that there is a statistically significant relationship between the pre- and posttests of psychological pressures in practices and non-practices and in favor of practices for sports activities, and has been used The researcher's experimental curriculum being the most suitable curriculum to solve the problem of research and achieve the objectives of research, but the research sample included 60 students from Diyala University for the academic year 2019-2020. at the beginning of the year, 30 students of practices were selected from the students of the Faculty of Sports Education (first stage) , and 30 non-practice students from various departments of the Faculty of Education, as the sample was selected in a random manner The researcher concluded that there is a statistically significant relationship between the pre- and post- tests of psychological pressures in practices and non-practices and in favor of practices for sports activities, and that the curriculum of the study of sports education showed positive results in relieving psychological pressures in practices, and the practice of sports activities helps the individual to empty emotions and turn them into a sports movement, which makes him feel psychological comfort, and recommends the researcher to certainly practice the lesson of sports education because of its positive effects on the psychology and behavior of the individual and turn his behavior from negative to positive, supporting the psychological aspect in the university stage through the exercise of sports activities.